Antioxidant activity of roasted and instant coffees: standardization and validation of methodologies - Vignoli, Josiane Alessandra; Bassoli, Denisley Gentil; Benassi, Marta de Toledo (Coffee Science - ISSN 1984-3909, 2012)
Antioxidant activity (AA) of coffee products has been widely discussed in recent years. The antioxidant potential, which has been related to the presence of different compounds, can be measured through several methodologies. However, the knowledge on the efficiency of these methods is still limited. This study standardized and validated several techniques of AA measurement (ABTS, FRAP, Folin-Ciocalteau, DPPH and Deoxyribose) for roasted and instant coffee. The results showed that all methods were accurate for evaluation of the AA: coefficients of variation between 3.5 and 10% were observed considering the two matrices (roasted and instant coffees) and the different concentrations applied. The concentration range must be carefully chosen for each product and method since it can interfere, depending on the methodology, in the accuracy and the AA values obtained.